Day of the Week Effect and the Stock Returns in the Colombo Stock Exchange: An Analysis of Empirical Evidence - Das, Bhagaban; Inun Jariya, A. M. (Indian Journal of Finance, 2009)
It has generally been assumed that the daily returns are the same for all days of the week. That is, expected return on a given stock is the same for Monday as it is for Tuesday as it is for Wednesday as it is for Thursday and as it is for Friday. However, a number of studies have uncovered the evidence that have been refused this belief. The day of the week effect is a phenomenon that constitutes a form of anomaly of the efficient capital market theory. This research study aims at analyzing the impact of day of the week effect on stock returns in the Colombo Stock Exchange. The main source of data for this research is the daily All Share Price Index of Colombo Stock Exchange for a sample period starting from 02nd January 1985 to 31st December 2004. To investigate the day of the week effect in relation to stock returns both descriptive statistics and autoregressive model were used. To test the day of the week effect four dummy variables, Tuesday through Friday, and five-lag variable to test lag effect have been introduced in the autoregressive model. The finding of the descriptive statistical analysis shows that there is a day of the week effect in stock returns at the Colombo Stock Exchange. However, the trend of this effect is not similar over the sample period. This may be due to the changing socio economic and political conditions of the island. The first finding of this research from the autoregressive model is that there is statistically significant day-of-the week-effect in stock returns of the Colombo Stock Exchange for the overall sample period, and Friday returns are significantly higher compared to the other days. The second finding is that there are lag effects existing in stock returns relating to the day of the week effect.